Models of Blended Learning: Organizational and Didactic Typology - V. I. Blinov; E. Yu. Esenina; I. S. Sergeev (Высшее образование в России)
The pandemic period revealed the shortcomings of distance learning, which do not allow it to be used as a basic form of education in the main educational programs. The most effective form of organizing the educational process, in the context of its digital transformation, is seen as blended learning, which involves alternating online and face-to-face learning  formats. The subject of this article is the pedagogical aspects of blended learning related to the organization of the process of mixed learning in an educational institution and its implementation in the joint activities of the teacher and students. The analysis of existing approaches to the identification and classification of blended learning models is carried out. The authors justify an approach to the typology of blended learning models, which can be implemented at different levels: curriculum, subject, section or topic (within the framework of the discipline), training session, extracurricular learning technology. The proposed methodology is based on the joint work of the network of experimental sites of the Ranepa Federal Institute for the Development of Education in the direction of “Digital Didactics”. The article shows the connection of the proposed  typology of organizational and didactic models of blended learning with other typologies and individual models presented in foreign and domestic  publications.